Recent decreases in domestic energy consumption in the United Kingdom attributed to human influence on the climate. (23rd June 2021) - Christidis, Nikolaos; McCarthy, Mark; Stott, Peter A.
Abstract: Domestic energy consumption in the United Kingdom depends on both meteorological and socio‐economic factors. The former are dominated by the effect of temperature during the colder months of the year, with the energy demand increasing as the temperature decreases. Warming of the UK climate under the influence of anthropogenic forcings is therefore expected to lead to a reduction in domestic energy consumption. Here, we present an end‐to‐end attribution study that investigates whether the anthropogenic effect on consumption is already evident in the United Kingdom. We analyse data of gas and electricity use in UK households during 2008–2019 and use a simple linear model to express the temperature dependence. Uncertainties in the resulting transfer functions are derived with a recent methodology, originally introduced for downscaling purposes, but adapted here for use in impact studies. The transfer functions are applied to temperature data from simulations with and without the effect of human influence on the climate, generated by 11 state‐of‐the‐art climate models. We thus assess the anthropogenic impact on energy consumption during the reference period by comparing it with what it might have been in a climate without anthropogenic climate change, but at the same level of adaptation. We find that without human influence on the climate, UK households would consume on average about 1, 400 kWh more per year, which would increase the annual energy bills by about 70 GBP. Our attribution assessment provides useful evidence of an impact that has already emerged, which can help inform UK's adaptation plans as the climate continues to warm. Abstract : Warming of the UK's climate is anticipated to lead to an overall reduction in domestic energy consumption. Empirical relationships between energy (electricity and gas) consumption and temperature are derived from observed data in years 2008–2019 and applied to simulated temperatures from Coupled Model Intercomparison Project phase 6 experiments with and without human influence on the climate. The analysis suggests that without the anthropogenic effect, UK households would consume about 1, 400 kWh more per year, which would increase the annual energy bills by about 70 GBP.